Study of the Level of Enzyme Muramidase and Some Biochemical Variable and Finding the Relationship between Them in Patients with Crohn`S Disease - Ali, Israa Tahseen; Yaseen, Amel Taha (American Journal of Biomedicine and Pharmacy, 2025)
Crohn’s disease is a chronic inflammatory condition affecting any part of the gastrointestinal tract, causing symptoms like abdominal pain and diarrhea. It affects millions worldwide, with higher prevalence in North America and Europe and its incidence continues to rise globally. Aim of study: The main objective of the current research study the relationship between specific biochemical parameters and Crohn` s disease in Mosul City. A cross study in a group of 70 as 48 males and 22 females participants with crohn` s disease and 70 healthy peoples 30 males, 40 females. Healthy participants by paid a visit outpatient clinics and private hospitals in Mosul city from the date of 19/1 to 25/2 of 2025. Whole blood samples were collected from all volunteers' patients and healthy to be analyze for serum Mur activity, TNF-α, MDA, GPx, PN and CAT. The results were showed that the majority patients with Crohn` s disease indicated higher levels of serum Mur activity in compared to healthy controls Also patients with Crohn` s disease having an increase of TNF, MDA, GPx, PN, CAT and decreases in levels of Fe,Se and Mn in patients with Crohn s disease.